Photoelectrical Characteristics of UV Organic Thin-film Transistor Detectors - Dao, Toan Thanh (VNU Journal of Science: Mathematics - Physics; Vol 33 No 2, 2017)
In this paper, a pentacene photo organic thin-film transistor (photoOTFT) was fabricated and characterized. The gate dielectric acted as a sensing layer thanks to it strongly absorbs UV light. Electrical behaviors of photoOTFT were measured under 365 nm UV illumination from the gate electrode side. The current in transistor channel was significantly enhanced by photoelectrons at interface of buffer/gate dielectric. Photosensitivity increased with the light intensity but decreased with the applied gate voltage. Meanwhile the photoresponsivity decreased with the light intensity and increased with the applied gate voltage. The transistor responses well with the pulse of light with many test cycles of light-on and light-off. The best photosensitivity, photoresponsivity, rising time and falling time parameters of the device were found to be about 10 4 , 0.12 A/W, and 0.2 s, respectively. The obtained photoelectrical results suggest that the photoOTFT can be a good candidate for practical uses in low-cost UV optoelectronics.